Targeting Hypoxia-Induced Oxidative Stress via Natural Antioxidant Modulation: From Cellular Signaling to Therapeutic Perspectives - Dwi Widyawati; Ghea Farmaning Thias Putri; Rifdah Hanifah; Firda Asmaul Husna; Nabila Aulia Tsaqifah; Ainina Al Shadrina (International Journal of Cell and Biomedical Science, 2025)
Hypoxia is a fundamental physiological and pathological condition that disrupts cellular homeostasis through the excessive generation of reactive oxygen species (ROS), leading to oxidative stress, inflammation, and organ dysfunction. The imbalance between ROS production and antioxidant defense mechanisms is a key contributor to cell injury and disease progression. This review aims to elucidate the molecular interactions among major redox-sensitive signaling pathways hypoxia-inducible factor 1 (HIF-1), nuclear factor kappa B (NF-κB), and nuclear factor erythroid 2-related factor 2 (Nrf2) in hypoxia-induced oxidative stress, and to highlight the therapeutic potential of natural antioxidants in modulating these pathways. Relevant literature published over the past five years (2020-2025) was systematically reviewed using databases including PubMed, Scopus, and ScienceDirect. The selected studies focused on molecular redox signaling, hypoxia-induced oxidative mechanisms, and the modulatory roles of natural phytochemicals such as Ficus carica bioactive compounds. Recent findings reveal that natural antioxidants regulate redox signaling by activating Nrf2-dependent antioxidant responses, suppressing NF-κB driven inflammation, and stabilizing HIF-1α under hypoxic conditions. Phytochemicals, particularly flavonoids and polyphenols, exhibit strong potential to restore oxidative balance, protect cellular integrity, and reduce hypoxia-induced damage. Modulating hypoxia-induced oxidative stress through natural antioxidant pathways offers a promising therapeutic strategy. A deeper understanding of the molecular crosstalk between redox signaling and phytochemical activity may provide new insights for developing preventive and therapeutic interventions against hypoxia-related disorders.